2010
DOI: 10.1016/j.pnpbp.2010.05.028
|View full text |Cite
|
Sign up to set email alerts
|

5-HTTLPR moderates effects of current life events on neuroticism: Differential susceptibility to environmental influences

Abstract: Research chronicling links between a polymorphism in the serotonin transporter gene (5-HTTLPR) and neuroticism has yielded inconsistent results. One possible explanation for this inconsistency is that any gene-phenotype association is obscured by a gene-X-environment (GXE) interaction. We studied a healthy non-clinical sample (N = 118) to determine whether the 5-HTTLPR interacts with current life events in predicting neuroticism. The differentialsusceptibility hypothesis led to the prediction of such an intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
84
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 46 publications
(51 reference statements)
12
84
0
Order By: Relevance
“…Both polymorphisms have also been associated with other personality traits and disorders, such as impulsiveness and impaired self-control, both of which are known to lead to elevated body weight and obesity (Terracciano et al 2009). This behavior may also be derive from biochemical alterations in areas of the brain responsible for emotional control (Lung et al 2011;Sookoian et al 2008;Cervilla et al 2006;Zalsman et al 2006;Pluess et al 2010;Fortier et al 2010). Subjects carrying the low activity-related 3R genotype of the MAOA uVNTR polymorphism have been reported to have increased aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both polymorphisms have also been associated with other personality traits and disorders, such as impulsiveness and impaired self-control, both of which are known to lead to elevated body weight and obesity (Terracciano et al 2009). This behavior may also be derive from biochemical alterations in areas of the brain responsible for emotional control (Lung et al 2011;Sookoian et al 2008;Cervilla et al 2006;Zalsman et al 2006;Pluess et al 2010;Fortier et al 2010). Subjects carrying the low activity-related 3R genotype of the MAOA uVNTR polymorphism have been reported to have increased aggressive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…5-HTTLPR is a 44-bp insertion/deletion polymorphism leading to either a short (S) or long (L) variant (Lesch et al 1993). It has been demonstrated that the S allele is associated with a 40 % decrease in transcriptional activity in vitro Lesch et al 1996;Hranilovic et al 2004) and is associated with anxiety, affective disorder, diabetes and obesity in both human and animal studies (Sookoian et al 2007; Lesch et al 1996;Collier et al 1996;Pluess et al 2010). Furthermore, this polymorphism has also been shown to be associated with nutritional impairment in female patients suffering from bulimia nervosa (Monteleone et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That said, it is important to go beyond the naive premise that the increase in vulnerability to major depression represented by the presence of copies of the polymorphic short variation of the SLC6A4 represents a direct effect of the serotonergic hypofunction. Current views of the nature-nurture structure of depression suggest that it is much more appropriately seem as a complex byproduct of an intensification of the vulnerability to a wide range of deleterious personality manifestations, which can be more specifically defined under the concept of neuroticism ( [33,34]; that is, of a personality style linked to negative emotional states and acute conflictive interactions.…”
Section: A Possible Solution To the Etiological Paradox Of Antisocialmentioning
confidence: 99%
“…A length polymorphism (5-HTTLPR) in the promoter region of the serotonin transporter gene, SLC6A4 [solute carrier family 6 (neurotransmitter transporter, serotonin), member 4, also referred to as 5-HTT], predicts increased observational fear conditioning (9) and amygdala activation in the presence of threatening social cues (10). This polymorphism, as well as a polymorphism in the promoter region of the serotonin 2A receptor gene, HTR2A [5-hydroxytryptamine (serotonin) receptor 2A, G protein-coupled, also referred to as 5-HT 2A ], is also associated with the personality dimension of neuroticism (11,12), increased risk for depression and other psychiatric disorders (13,14), and increased cortisol response to a psychosocial stressor (12,15). Intriguingly, a recent assessment of global variation at SLC6A4 and HTR2A suggests unusual evolutionary histories at these loci in humans (16).…”
mentioning
confidence: 99%